MENJADI ISTRI DIPLOMAT: HURUSTIATI SOEBANDRIO DALAM MEMBENTUK CITRA INDONESIA DI INGGRIS 1947-1954 - Ayu Wulandari (Handep: Jurnal Sejarah dan Budaya, 2021)
In the history of Indonesian diplomacy, there have been several outstanding diplomat figures who have made achievements, such as Soebandrio. Then, it is important to realize that the success of Soebandrio in connecting Indonesia with the world when he was in London and Moscow; and his role in various significant state missions cannot be apart from his wife’s role, Hurustiati Soebandrio. During Soebandrio’s career, Hurustiati’s diplomatic role began when her husband became the Indonesian Ambassador in London, at least from 1947 to 1954. During that time, Hurustiati took part in various efforts to build a good image of Indonesia to support the implementation of foreign policy. This study focuses on examining the role of Hurustiati Soebandrio as a wife of a diplomat from 1947 to 1954. Therefore, the study aims to present the role of women as diplomatic wives in the writing of the history of Indonesian diplomacy. In general, it also aims to encourage the writing of a history of diplomacy that pays attention to the role of women. This study employed the historical method by placing archives, magazines, and newspapers as primary sources. The study shows three images of Indonesia that Hurustiati formed in London, namely Indonesia as an independent country, a country that try to reach gender equality, and a multicultural county. To achieve these three images, Hurustiati made various efforts, such as giving official lectures, holding talks with diplomatic officials and their wives, and initiating exhibitions.